First pass metabolism of ethanol is strikingly influenced by the speed of gastric emptying. Issue 5 (1st November 1998) - Oneta, C M; Simanowski, U A; Martinez, M; Allali-Hassani, A; Parés, X; Homann, N; Conradt, C; Waldherr, R; Fiehn, W; Coutelle, C; Seitz, H K
Abstract : Background —Ethanol undergoes a first pass metabolism (FPM) in the stomach and liver. Gastric FPM of ethanol primarily depends on the activity of gastric alcohol dehydrogenase (ADH). In addition, the speed of gastric emptying (GE) may modulate both gastric and hepatic FPM of ethanol. Aims —To study the effect of modulation of GE on FPM of ethanol in the stomach and liver. Methods —Sixteen volunteers (eight men and eight women) received ethanol (0.225 g/kg body weight) orally and intravenously, and the areas under the ethanol concentration time curves were determined to calculate FPM of ethanol. In seven of these subjects, FPM of ethanol was measured after the intravenous administration of 10 mg metoclopramide (MCP) and 20 mg N -butylscopolamine (NBS) in separate experiments to either accelerate or delay GE. GE was monitored sonographically by integration of the antral area of the stomach every five minutes for 90 minutes after oral ethanol intake. In addition, gastric biopsy specimens were taken to determine ADH activity and phenotype, as well as to evaluate gastric histology. Blood was also drawn for ADH genotyping. Results —GE time was significantly delayed by the administration of NBS as compared with controls (p<0.0001) and as compared with the administration of MCP (p<0.0001). This was associated with a significantly enhanced FPM of ethanol with NBS compared with MCP (p = 0.0004). A significant correlation was noted between GE time and FPM of ethanol ( r = 0.43, p = 0.0407). Gastric ADH activity did not significantly correlate with FPM of ethanol. Conclusion —FPM of ethanol is strikingly modulated by the speed of GE. Delayed GE increases the time of exposure of ethanol to gastric ADH and may therefore increase gastric FPM of ethanol. In addition, hepatic FPM of ethanol may also be enhanced as the result of slower absorption of ethanol from the small intestine. Thus a knowledge of GE time is a major prerequisite for studying FPM of ethanol in humans.